Effect of different seedling weights on Kappaphycus alvarezii growth. Issue 1 (October 2021) - Irfan, M; Abdullah, N; La Ujiara, W
Abstract: Seaweed K. alvarezii is one of leading commodities in aquaculture because this seaweed species produces carrageenan which has high economic value. This study aimed to determine effect of different seedling weights on the growth of seaweed K. alvarezii, and to determine which seedling weight had the best effect on seaweed growth. Planting process was carried out using longline method. Size of longline construction used was 10 m x 20 m, with a length of 20 m and a distance of 1 m between each ropes. Each rope line contained about 66 clumps of seedlings with a distance between clumps of 15 cm. Thallus weight used was 30 gr, 50 gr, 70 gr for each treatment. The highest mean value of absolute weight growth of seaweed K. alvarezii was found in treatment C (thallus weight 70 gr) with an average value of 99.27 gr, followed by treatment A (thallus weight 30 gr) of 51.95 gr and the lowest value found in treatment B (thallus weight 50 gr) of 51.65 gr.